Towards a circular bioeconomy to produce methane by co-digestion of coffee and brewery waste using a mixture of anaerobic granular sludge and cattle manure as inoculum - Rodrigues, Caroline Varella (2024)
Coffee processing wastes, such as solid (pulp and husk) and wastewater, co-digested with industrial brewery wastewater, serve as excellent substrates for generating methane in the anaerobic digestion process. This study compared methane production using different compositions of cattle manure (CM) and granular sludge from an Upflow Anaerobic Sludge Blanket (UASB) reactor used in poultry wastewater treatment (GS). Four anaerobic batch reactors (500 mL) were assembled, A (50% CM and 50% GS), B (60% CM and 40% GS), C (70% CM and 30% of GS) and D (60% CM and 40% GS). Equal concentrations of substrates were added to all reactors: pulp and husk pretreated by hydrothermolysis (1 g L−1), coffee (10 g COD L−1) and brewery (1.5 g COD L−1) wastewaters. Assays A, B and C were supplemented with 2 g L−1 of yeast extract, except for assay D. The reactors were operated at 37 °C and pH 7.0. In assay B, the highest CH4 production of 759.15 ± 19.20 mL CH4 g−1 TS was observed, possibly favored by the synergistic interactions between cellulolytic bacteria Christensenellaceae_R-7_group and Methanosaeta archaea, as inferred by genes encoding enzymes related to acetoclastic methanogenesis (acetyl-CoA synthetase). Consequently, the electricity production potential of assay B (45614.08 kWh−1 year−1) could meet the energy demand of a farm producing coffee and beer, contributing to a positive energy balance concerning methane generation.